A cross-linking agent for fracturing and preparation method thereof

By modifying porous organic polymers and organic boron cross-linking components, a cross-linking agent for fracturing was prepared, which solved the temperature resistance and cost problems of guar gum fracturing fluid, achieved more efficient cross-linking and a more stable gel structure, and adapted to high temperature environments.

CN120230533BActive Publication Date: 2025-09-09XIAN THREE-DIMENSIONAL TECH DEV CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510718328.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-09-09
Estimated Expiration
2045-05-30

AI Technical Summary

Technical Problem

Existing guar gum fracturing fluids damage reservoir permeability at high concentrations and are costly, while low concentrations affect the fracturing fluid effect and recovery rate, and the temperature resistance of existing nano-crosslinkers is not ideal.

Method used

By modifying porous organic polymers and organic boron cross-linking components to form a high-density BO bond cross-linking structure, dopamine modification is used to provide amino/hydroxyl active sites to prepare a cross-linking agent for fracturing, thereby improving cross-linking efficiency and enhancing temperature resistance.

Benefits of technology

It improves the cross-linking efficiency of guar gum and the temperature resistance of fracturing fluid, forms a tighter gel structure, improves the viscosity and stability of fracturing fluid, and adapts to high temperature environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120230533B_ABST
    Figure CN120230533B_ABST
Patent Text Reader

Abstract

The present invention provides a kind of cross-linking agent for fracturing and preparation method thereof, belong to the field of oilfield chemical technology, comprise the steps:Borax, glycerine, deionized water, sodium hydroxide, erythritol are mixed, high temperature stirring prepares organic boron cross-linking component;Formaldehyde, methylglyoxal and acetic acid aqueous solution are mixed, are added dropwise to 4,4',4''-(1,3,5-triazine-2,4,6-triyl) triphenylamine solution, pyroreaction, purification obtains porous organic polymer;Porous organic polymer and deionized water are mixed, ultrasonic treatment, dopamine is added, pH value is adjusted with NaOH solution, stirring reaction, purification obtains modified porous carrier;Modified porous carrier is added to deionized water ultrasonic treatment, organic boron cross-linking component high temperature stirring is added, vacuum drying obtains cross-linking agent for fracturing.The present invention can improve the cross-linking efficiency of guar gum, and has the effect of promoting the temperature resistance of fracturing fluid system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of oilfield chemistry, and in particular to a cross-linking agent for fracturing and a preparation method thereof. Background Art

[0002] During fracturing operations, the primary function of fracturing fluid is to create fractures and carry proppant, ensuring fracture stability and improving oil and gas recovery. Currently, guar gum fracturing fluid is the most commonly used water-based fracturing fluid system, primarily due to its low cost, high safety, and wide applicability. Water-based fracturing fluids are formulated by adding a variety of additives to water, such as stabilizers, crosslinkers, breakers, and drainage agents.

[0003] Guar gum fracturing fluid is the most widely used water-based system. Its advantages include strong thickening capacity, excellent temperature and shear resistance, and low fluid loss, making it a key component in fracturing operations in oil and gas fields. Generally, guar gum is used at a concentration between 0.3% and 0.6%. However, while higher guar gum concentrations can improve fracturing fluid performance, they also produce insoluble residues, potentially impairing reservoir permeability and increasing oil and gas production costs. Therefore, reducing guar gum concentration is an effective way to reduce costs. However, excessively low concentrations can compromise the effectiveness of the fracturing fluid, potentially affecting the success of the fracturing operation and subsequent oil and gas recovery.

[0004] To balance performance and cost, current research focuses on developing high-performance crosslinkers. By optimizing the crosslinker structure, the crosslinking efficiency of guar gum can be increased, thereby reducing its concentration without sacrificing fracturing fluid performance. This approach not only reduces fracturing costs but also increases the success rate of fracturing operations and oil and gas well recovery.

[0005] Nanoparticles are often used due to their unique properties. Surface modification using active groups on their surfaces can form nanofunctional compounds. Patent application publication number CN111139053A discloses a nanosilica organoboron crosslinker and its preparation method. By modifying nanosilica with phenylboronic acid, the surface is modified to form multiple crosslinking sites, thereby improving crosslinking performance and reducing guar gum usage, thereby lowering fracturing costs. However, this crosslinker still suffers from unsatisfactory heat resistance when used to prepare guanidine jelly or hydroxypropyl guanidine jelly.

[0006] Therefore, it is necessary to provide a cross-linking agent for fracturing and a preparation method thereof to solve the problems existing in the above-mentioned prior art. Summary of the Invention

[0007] In view of this, the present invention provides a cross-linking agent for fracturing and a preparation method thereof, which can improve the cross-linking efficiency of guar gum and have the effect of improving the temperature resistance of the fracturing fluid system.

[0008] To achieve the above object, the present invention provides a method for preparing a cross-linking agent for fracturing, comprising the following steps:

[0009] S1. Mix borax, glycerol and deionized water, add sodium hydroxide and stir at high temperature, add erythritol and glycerol, and stir at high temperature to prepare an organic boron cross-linking component;

[0010] S2, after formaldehyde, methylglyoxal and acetic acid aqueous solution are mixed, the mixture is dropped into 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution, reacted at high temperature, purified, and vacuum dried to obtain a porous organic polymer;

[0011] S3, mixing the porous organic polymer and deionized water, ultrasonically treating the mixture, adding dopamine, adjusting the pH value with a NaOH solution, stirring the mixture for reaction, purifying the mixture, and vacuum drying the mixture to obtain a modified porous support;

[0012] S4. Add the modified porous carrier into deionized water, perform ultrasonic treatment, add the organic boron cross-linking component, stir at high temperature, wash, and vacuum dry to obtain a cross-linking agent for fracturing.

[0013] The present invention modifies borax. Borate, under the action of sodium hydroxide, releases boric acid groups, which then react with hydroxyl groups in glycerol and erythritol to form a three-dimensional crosslinked structure, serving as an organoboron crosslinking component. Erythritol contains four hydroxyl groups, which, when combined with borate, creates a higher density of BO bonds in the organoboron crosslinking component, resulting in a stronger crosslinked structure. This provides more crosslinking sites, improving the material's heat resistance and shear resistance. It also further enhances the crosslinking efficiency with guar gum, helps connect distant guar gum molecules, promotes the formation of a jelly structure, and enhances its stability and heat resistance.

[0014] The present invention uses 4,4',4''-(1,3,5-triazine-2,4,6-triyl) triphenylamine, methylglyoxal and formaldehyde as reactive monomers to synthesize a porous organic polymer, and uses dopamine to modify it as a carrier of an organic boron cross-linking component, and finally prepares a cross-linking agent for fracturing. The porous organic polymer provides a high specific surface area, chemical stability and high temperature resistance, further improving the stability of the cross-linking agent at high temperatures. The modification of dopamine provides amino / hydroxyl active sites, and the amino group can form an ionic bond with the guar gum carboxylate, which also makes the overall dispersion in water better. Moreover, the larger-sized nano cross-linker has more cross-linking sites, which helps to more efficiently adsorb or cross-link other molecules in the solution, cross-link with the guar gum molecules, and increase the efficiency of the cross-linking reaction. In addition, the organic boron cross-linking component loaded in the pores can achieve the delayed release of borate ions, thereby maintaining its cross-linking reaction with the guar gum molecules for a longer time, and the synergistic effect of each component makes the frozen structure formed tighter, further improving the temperature resistance and shear resistance of the frozen gel.

[0015] Optionally, in step S1, borax, glycerol and deionized water are mixed, sodium hydroxide is added, and the mixture is stirred at 65-85° C. for 10-20 minutes, and then erythritol and glycerol are added, and the mixture is stirred at a low speed at 75-85° C. for 5-7 hours to obtain an organic boron cross-linking component.

[0016] In the process of preparing the organic boron cross-linking component of the present invention, the addition of glycerol can also improve the stability of the solution and avoid precipitation.

[0017] Optionally, the 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution is obtained by mixing 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine and an acetic acid aqueous solution with a molar concentration of 4 mol / L, and stirring at 25° C. until completely dissolved.

[0018] Optionally, the molar concentration of the acetic acid aqueous solution is 4 mol / L.

[0019] Optionally, the high temperature reaction temperature in step S2 is 80-90° C. and the reaction time is 10-12 h.

[0020] Optionally, in step S2, after the high-temperature reaction, the product is dialyzed and purified using a dialysis membrane for 2 to 3 days, and then vacuum-dried at 60° C. for 12 hours to obtain the porous organic polymer.

[0021] The present invention utilizes a dialysis membrane to perform dialyzation purification on the product to remove residual monomers and improve the purity of the final product.

[0022] Optionally, in step S3, linolenic acid is added and mixed at the same time as dopamine. After mixing, the pH value is adjusted to 8-9 with NaOH solution, and the mixture is stirred and reacted at 25°C for 12 hours. After purification by dialyzing with a dialysis membrane for 3 days, the mixture is vacuum dried at 60°C for 12 hours to obtain a modified porous carrier.

[0023] The present invention also incorporates linolenic acid during the preparation of the modified porous carrier. The introduction of linolenic acid can form more functional groups on the surface of the porous organic polymer. These functional groups interact more strongly with the active groups in the organoboron crosslinking component, thereby promoting the loading of the organoboron crosslinking component. Simultaneously, the unsaturated double bonds in the linolenic acid molecules can participate in the crosslinking reaction of guar gum, forming a three-dimensional crosslinked network and further increasing the overall crosslinking strength. This not only improves the viscosity, stability, and fluidity of the fracturing fluid, but also enables it to better adapt to high-temperature environments.

[0024] Optionally, the molar concentration of the NaOH solution is 0.1 mol / L, and the ultrasonic treatment time is 5 to 10 min.

[0025] Optionally, in step S4, the ultrasonic treatment time is 5 to 10 minutes, the high-temperature stirring temperature is 85° C. and the time is 2 to 3 hours, the vacuum drying temperature is 60 to 80° C. and the time is 10 to 12 hours, and the detergent used for washing is anhydrous ethanol.

[0026] The present invention uses anhydrous ethanol for washing to help remove unreacted residues and ensure the purity of the final product.

[0027] Optionally, the cross-linking agent for fracturing comprises the following raw materials in parts by mass: 2-3 parts of modified porous carrier and 15-20 parts of organic boron cross-linking component.

[0028] The present invention adopts the above-mentioned mass fraction matching ratio, which can achieve a higher proportion of organic boron cross-linking components loaded on the modified porous carrier, further improving the overall performance, so that it can increase the cross-linking efficiency of guar gum, and has a certain effect of improving the temperature resistance of the fracturing fluid system.

[0029] The above technical solution of the present invention includes at least the following beneficial effects:

[0030] 1. The present invention modifies borax through hydrolysis and complexation reactions to form a tetracoordinated organoboron crosslinking component. The borate solution crosslinks with erythritol, and the four hydroxyl groups of erythritol bind to the borax, forming a high-density BO crosslinked structure. This improves the crosslinking efficiency with guar gum while enhancing the stability and high-temperature resistance of the jelly structure.

[0031] 2. This invention prepares a porous organic polymer and uses dopamine as a carrier for an organoboron crosslinking component to prepare a crosslinker for fracturing. This material exhibits high specific surface area, chemical stability, and high-temperature resistance. The dopamine modification provides amino / hydroxyl active sites, enhancing crosslinking efficiency with guar gum. The loading of the organoboron crosslinking component delays borate ion release, maintains the crosslinking reaction, improves the temperature and shear resistance of the gel, and forms a more compact gel structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a diagram of the hanging state of the jelly obtained by using the cross-linking agent for fracturing prepared in Example 6 of the present invention;

[0033] Figure 2 This is a temperature resistance curve of the jelly obtained by using the cross-linking agent for fracturing prepared in Example 6 of the present invention. DETAILED DESCRIPTION

[0034] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention. All other embodiments obtained by ordinary technicians in this field based on the described embodiments of the present invention are within the scope of protection of the present invention.

[0035] Example 1

[0036] 24 g of borax, 10 mL of glycerol and 40 mL of deionized water were mixed evenly, 5 g of sodium hydroxide was added, and the mixture was stirred at 85° C. for 15 min until the borax was completely dissolved. Then, 18 parts of erythritol and 5 parts of glycerol were added and stirred at a low speed at 85° C. for 7 h to prepare an organic boron cross-linking component.

[0037] 11 g of 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine was added to 500 mL of an aqueous acetic acid solution having a molar concentration of 4 mol / L, and the mixture was stirred at 25°C until completely dissolved to obtain a 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution. 14.2 g of formaldehyde, 32.8 g of methylglyoxal, and 300 mL of an aqueous acetic acid solution having a molar concentration of 4 mol / L were mixed and stirred for 30 minutes to obtain a mixed solution. 152 mL of the mixed solution was then dropwise added to the 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution, and the reaction was continued at 90°C for 12 hours. Then, the product was dialyzed and purified using a dialysis membrane (molecular weight cutoff: 3500Da) for 3 days, and finally vacuum dried at 60°C for 12 hours to obtain a porous organic polymer; 5g of the porous organic polymer was added to 250mL of deionized water at 100°C, ultrasonically treated for 10 minutes, and then 2g of dopamine and 0.5mL of linolenic acid were added and mixed, and the pH value was adjusted to 9 with a NaOH solution with a molar concentration of 0.1mol / L. After stirring and reacting at 25°C for 12 hours, the product was dialyzed and purified using a dialysis membrane (molecular weight cutoff: 3500Da) for 3 days, and vacuum dried at 60°C for 12 hours to obtain a modified porous carrier.

[0038] 2 g of the modified porous carrier was added to 100 mL of deionized water, ultrasonically treated for 10 min, 20 mL of the organic boron cross-linking component was added, stirred at 85° C. for 3 h, washed with anhydrous ethanol, and vacuum dried at 60° C. for 12 h to obtain a cross-linking agent for fracturing.

[0039] Example 2

[0040] 20 g of borax, 10 mL of glycerol and 40 mL of deionized water were mixed evenly, 5 g of sodium hydroxide was added, and the mixture was stirred at 65° C. for 15 min until the borax was completely dissolved. Then, 15 parts of erythritol and 3 parts of glycerol were added and stirred at low speed at 75° C. for 7 h to prepare an organic boron cross-linking component.

[0041] 11 g of 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine was added to 500 mL of an aqueous acetic acid solution having a molar concentration of 4 mol / L, and the mixture was stirred at 25°C until completely dissolved to obtain a 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution. 14.2 g of formaldehyde, 32.8 g of methylglyoxal, and 300 mL of an aqueous acetic acid solution having a molar concentration of 4 mol / L were mixed and stirred for 15 minutes to obtain a mixed solution. 136 mL of the mixed solution was then dropwise added to the 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution, and the reaction was continued at 80°C for 12 hours. Then, the product was dialyzed and purified for 2 days using a dialysis membrane (molecular weight cutoff: 3500Da), and finally vacuum dried at 60°C for 12 hours to obtain a porous organic polymer; 5 g of the porous organic polymer was added to 250 mL of deionized water at 100°C, ultrasonically treated for 5 minutes, and then 1.8 g of dopamine and 0.2 mL of linolenic acid were added and mixed, and the pH value was adjusted to 8 with a NaOH solution with a molar concentration of 0.1 mol / L. After stirring and reacting at 25°C for 12 hours, the product was dialyzed and purified for 3 days using a dialysis membrane (molecular weight cutoff: 3500Da), and vacuum dried at 60°C for 12 hours to obtain a modified porous carrier.

[0042] 2.2 g of the modified porous support was added to 100 mL of deionized water, ultrasonically treated for 5 min, 15 mL of an organic boron cross-linking component was added, stirred at 85° C. for 2 h, washed with anhydrous ethanol, and vacuum dried at 80° C. for 10 h to obtain a cross-linking agent for fracturing.

[0043] Example 3

[0044] 25 g of borax, 10 mL of glycerol and 40 mL of deionized water were mixed evenly, 5 g of sodium hydroxide was added, and the mixture was stirred at 70° C. for 10 min until the borax was completely dissolved. Then, 16 parts of erythritol and 3 parts of glycerol were added and stirred at low speed at 80° C. for 6 h to prepare an organic boron cross-linking component.

[0045] 11 g of 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine was added to 500 mL of an aqueous acetic acid solution having a molar concentration of 4 mol / L, and the mixture was stirred at 25°C until completely dissolved to obtain a 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution. 14.2 g of formaldehyde, 32.8 g of methylglyoxal, and 300 mL of an aqueous acetic acid solution having a molar concentration of 4 mol / L were mixed and stirred for 20 minutes to obtain a mixed solution. 145 mL of the mixed solution was then dropwise added to the 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution, and the reaction was continued at 80°C for 12 hours. Then, the product was dialyzed and purified using a dialysis membrane (molecular weight cutoff: 3500Da) for 3 days, and finally vacuum dried at 60°C for 12 hours to obtain a porous organic polymer; 5g of the porous organic polymer was added to 250mL of deionized water at 100°C and ultrasonically treated for 6 minutes, and then 1.5g of dopamine and 0.3mL of linolenic acid were added and mixed, and the pH value was adjusted to 8.4 with a NaOH solution with a molar concentration of 0.1mol / L, and the reaction was stirred at 25°C for 12 hours, and then dialyzed and purified using a dialysis membrane (molecular weight cutoff: 3500Da) for 3 days, and then vacuum dried at 60°C for 12 hours to obtain a modified porous carrier.

[0046] 2.5 g of the modified porous support was added to 100 mL of deionized water, ultrasonically treated for 8 min, 17 mL of the organic boron cross-linking component was added, stirred at 85° C. for 2.5 h, washed with anhydrous ethanol, and vacuum dried at 65° C. for 11 h to obtain a cross-linking agent for fracturing.

[0047] Example 4

[0048] 23 g of borax, 10 mL of glycerol and 40 mL of deionized water were mixed evenly, 5 g of sodium hydroxide was added, and the mixture was stirred at 75° C. for 15 minutes until the borax was completely dissolved. Then, 15 parts of erythritol and 3.5 parts of glycerol were added and stirred at a low speed at 80° C. for 6.5 hours to prepare an organic boron cross-linking component.

[0049] 11 g of 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine was added to 500 mL of an aqueous acetic acid solution having a molar concentration of 4 mol / L, and the mixture was stirred at 25°C until completely dissolved to obtain a 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution. 14.2 g of formaldehyde, 32.8 g of methylglyoxal, and 300 mL of an aqueous acetic acid solution having a molar concentration of 4 mol / L were mixed and stirred for 20 minutes to obtain a mixed solution. 147 mL of the mixed solution was then dropwise added to the 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution, and the reaction was continued at 85°C for 12 hours. Then, the product was dialyzed and purified for 2 days using a dialysis membrane (molecular weight cutoff: 3500Da), and finally vacuum dried at 60°C for 12 hours to obtain a porous organic polymer; 5g of the porous organic polymer was added to 250mL of deionized water at 100°C and ultrasonically treated for 8 minutes, and then 1.9g of dopamine and 0.3mL of linolenic acid were added and mixed, and the pH value was adjusted to 8.2 with a NaOH solution with a molar concentration of 0.1mol / L, and the reaction was stirred at 25°C for 12 hours, and then dialyzed and purified for 3 days using a dialysis membrane (molecular weight cutoff: 3500Da), and vacuum dried at 60°C for 12 hours to obtain a modified porous carrier.

[0050] 2.6 g of the modified porous support was added to 100 mL of deionized water, ultrasonically treated for 8 min, 18 mL of the organic boron cross-linking component was added, stirred at 85° C. for 2.5 h, washed with anhydrous ethanol, and vacuum dried at 80° C. for 10 h to obtain a cross-linking agent for fracturing.

[0051] Example 5

[0052] 21 g of borax, 10 mL of glycerol and 40 mL of deionized water were mixed evenly, 5 g of sodium hydroxide was added, and the mixture was stirred at 70° C. for 16 min until the borax was completely dissolved. Then, 17 parts of erythritol and 4 parts of glycerol were added and stirred at a low speed at 85° C. for 5.5 h to prepare an organic boron cross-linking component.

[0053] 11 g of 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine was added to 500 mL of an aqueous acetic acid solution having a molar concentration of 4 mol / L, and the mixture was stirred at 25°C until completely dissolved to obtain a 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution. 14.2 g of formaldehyde, 32.8 g of methylglyoxal, and 300 mL of an aqueous acetic acid solution having a molar concentration of 4 mol / L were mixed and stirred for 25 minutes to obtain a mixed solution. 136 mL of the mixed solution was then dropwise added to the 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution, and the reaction was continued at 85°C for 12 hours. Then, the product was dialyzed and purified using a dialysis membrane (molecular weight cutoff: 3500Da) for 3 days, and finally vacuum dried at 60°C for 12 hours to obtain a porous organic polymer; 5g of the porous organic polymer was added to 250mL of deionized water at 100°C and ultrasonically treated for 6 minutes, and then 1.8g of dopamine and 0.4mL of linolenic acid were added and mixed, and the pH value was adjusted to 8.5 with a NaOH solution with a molar concentration of 0.1mol / L. After stirring and reacting at 25°C for 12 hours, it was dialyzed and purified using a dialysis membrane (molecular weight cutoff: 3500Da) for 3 days, and then vacuum dried at 60°C for 12 hours to obtain a modified porous carrier.

[0054] 3 g of the modified porous carrier was added to 100 mL of deionized water, ultrasonically treated for 10 min, 20 mL of the organic boron cross-linking component was added, stirred at 85° C. for 2 h, washed with anhydrous ethanol, and vacuum dried at 60° C. for 12 h to obtain a cross-linking agent for fracturing.

[0055] Example 6

[0056] 25 g of borax, 10 mL of glycerol and 40 mL of deionized water were mixed evenly, 5 g of sodium hydroxide was added, and the mixture was stirred at 65° C. for 20 min until the borax was completely dissolved. Then, 15 parts of erythritol and 5 parts of glycerol were added and stirred at low speed at 80° C. for 6 h to prepare an organic boron cross-linking component.

[0057] 11 g of 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine was added to 500 mL of an aqueous acetic acid solution having a molar concentration of 4 mol / L, and the mixture was stirred at 25°C until completely dissolved to obtain a 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution. 14.2 g of formaldehyde, 32.8 g of methylglyoxal, and 300 mL of an aqueous acetic acid solution having a molar concentration of 4 mol / L were mixed and stirred for 30 minutes to obtain a mixed solution. 152 mL of the mixed solution was then dropwise added to the 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution, and the reaction was continued at 80°C for 12 hours. Then, the product was dialyzed and purified for 2 days using a dialysis membrane (molecular weight cutoff: 3500Da), and finally vacuum dried at 60°C for 12 hours to obtain a porous organic polymer; 5g of the porous organic polymer was added to 250mL of deionized water at 100°C, ultrasonically treated for 8 minutes, and then 2g of dopamine and 0.2mL of linolenic acid were added and mixed, and the pH value was adjusted to 9 with a NaOH solution with a molar concentration of 0.1mol / L. After stirring and reacting at 25°C for 12 hours, the product was dialyzed and purified for 3 days using a dialysis membrane (molecular weight cutoff: 3500Da), and vacuum dried at 60°C for 12 hours to obtain a modified porous carrier.

[0058] 3 g of the modified porous carrier was added to 100 mL of deionized water, ultrasonically treated for 10 min, 17 mL of the organic boron cross-linking component was added, stirred at 85° C. for 3 h, washed with anhydrous ethanol, and vacuum dried at 80° C. for 11 h to obtain a cross-linking agent for fracturing.

[0059] The present invention also carried out comparative examples and related tests.

[0060] Comparative Example 1

[0061] Compared with Example 6, the only difference is that the porous organic polymer is not modified. The other preparation methods and components are completely consistent, and the cross-linking agent for fracturing is finally prepared.

[0062] Comparative Example 2

[0063] Compared with Example 6, the only difference is that ethylene glycol is used instead of erythritol to prepare the organic boron cross-linking component. The other preparation methods and components are completely consistent, and finally a cross-linking agent for fracturing is prepared.

[0064] Comparative Example 3

[0065] Nano-silica organic boron cross-linking agent was prepared as a cross-linking agent for fracturing according to the preparation method of the patent application document with publication number CN111139053A.

[0066] Performance testing

[0067] According to the Chinese petroleum and natural gas industry standard SY / T6216-1996 "Test Method for Performance of Cross-linking Agents for Fracturing", the cross-linking agents for fracturing prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were tested for delayed cross-linking performance, hanging performance, and temperature resistance. The results are shown in Table 1.

[0068] Table 1

[0069]

[0070] As shown in Table 1, the delayed crosslinking performance, hanging performance and temperature resistance of the crosslinking agents prepared using Examples 1 to 6 in guar gum fracturing fluid are significantly better than those of Comparative Examples 1 to 3, and meet the requirements specified in SY / T6376-2008 "General Technical Conditions for Fracturing Fluids".

[0071] According to the test data analysis in Table 1, in Comparative Example 1, due to the unmodified carrier, the organic boron component is released quickly, resulting in a delay time of only 20s, and due to the weak binding force of the unmodified carrier, the cross-linking density of each component is low, resulting in a poor hanging state and a significant decrease in heat resistance. In addition, Comparative Example 2 uses ethylene glycol instead of erythritol, and the hydroxyl density is reduced, resulting in a decrease in cross-linking stability, making its hanging state and heat resistance poor. Comparative Example 3 has poor dispersion and easy agglomeration of nano-silica, resulting in overall performance worse than Example 6. In summary, the cross-linking agent for fracturing prepared by the preparation method of the present invention has the best effect during use, among which, Figure 1 This is a photo of the hanging state of the jelly obtained by using the cross-linking agent for fracturing prepared in Example 6. Figure 2 Its temperature resistance curve shows that its temperature resistance can reach 192℃, and the residual viscosity of the gel is reduced to 50mPa·s at 192℃.

[0072] The above is a preferred embodiment of the present invention. Those skilled in the art may make several improvements and modifications without departing from the principles of the present invention. These improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a cross-linking agent for fracturing, characterized in that: The steps include: S1. Mix borax, glycerol, and deionized water, add sodium hydroxide, and stir at 65-85° C., add erythritol and glycerol, and stir at 75-85° C. to prepare an organic boron cross-linking component; S2, after formaldehyde, methylglyoxal and acetic acid aqueous solution are mixed, the mixture is dropped into 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution, reacted at 80-90°C, purified, and vacuum dried to obtain a porous organic polymer; S3, mixing the porous organic polymer with deionized water, ultrasonically treating the mixture, adding dopamine and linolenic acid, adjusting the pH value with a NaOH solution, stirring the mixture for reaction, purifying the mixture, and vacuum drying the mixture to obtain a modified porous support; S4, adding the modified porous support to deionized water, ultrasonically treating it, adding the organic boron cross-linking component, stirring at 85° C., washing it, and vacuum drying it to obtain a cross-linking agent for fracturing; The 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine solution is prepared by mixing 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine and an acetic acid aqueous solution having a molar concentration of 4 mol / L, and stirring at 25° C. until the mixture is completely dissolved.

2. The method for preparing a cross-linking agent for fracturing according to claim 1, characterized in that: In step S1, borax, glycerol and deionized water are mixed, sodium hydroxide is added, and the mixture is stirred at 65-85° C. for 10-20 minutes. Then, erythritol and glycerol are added, and the mixture is stirred at a low speed at 75-85° C. for 5-7 hours to prepare an organic boron cross-linking component.

3. The method for preparing a cross-linking agent for fracturing according to claim 1, characterized in that: The molar concentration of the acetic acid aqueous solution is 4 mol / L.

4. The method for preparing a cross-linking agent for fracturing according to claim 1, characterized in that: The high temperature reaction temperature in step S2 is 80-90° C. and the reaction time is 10-12 hours.

5. The method for preparing a cross-linking agent for fracturing according to claim 1, characterized in that: In the step S2, after reacting at 80-90° C., the mixture is dialyzed and purified using a dialysis membrane for 2-3 days, and then vacuum-dried at 60° C. for 12 hours to obtain a porous organic polymer.

6. The method for preparing a cross-linking agent for fracturing according to claim 1, characterized in that: In step S3, dopamine and linolenic acid are added and mixed, and after mixing, the pH value is adjusted to 8-9 with NaOH solution, and the mixture is stirred and reacted at 25°C for 12 hours, and then dialyzed and purified with a dialysis membrane for 3 days, and vacuum dried at 60°C for 12 hours to obtain a modified porous carrier.

7. The method for preparing a cross-linking agent for fracturing according to claim 1, characterized in that: The molar concentration of the NaOH solution is 0.1 mol / L, and the ultrasonic treatment time is 5 to 10 minutes.

8. The method for preparing a cross-linking agent for fracturing according to claim 1, characterized in that: In step S4, the ultrasonic treatment time is 5-10 minutes, the stirring time is 2-3 hours, the vacuum drying temperature is 60-80° C. and the time is 10-12 hours, and the detergent used for washing is anhydrous ethanol.

9. A cross-linking agent for fracturing, prepared by the method for preparing a cross-linking agent for fracturing according to any one of claims 1 to 8, characterized in that: The method comprises the following raw materials in parts by mass: 2-3 parts of a modified porous carrier and 15-20 parts of an organic boron cross-linking component.

Citation Information

Patent Citations

  • Nano silicon dioxide organic boron cross-linking agent and preparation method thereof

    CN111139053A

  • 200 DEG C high temperature resistance fracturing construction jelly preparation method

    CN105131931A

  • Cross-linking agent for reconstructed wellbore fracturing as well as preparation method and application of cross-linking agent

    CN114032083A